Influence of the Method of Treatment of Samples of Biological Nature on the Results of Determination of Heavy Metals by Atomic Emission Spectroscopy - E. N. Blokhina; N. V. Kelus; V. S. Chuchalin (Разработка и регистрация лекарственных средств)
Introduction. The article is devoted to the relevance of choosing sample preparation method for heavy metals concentration determination in biological sample by using atomic emission spectrometry. Much attention is given to compare 2 methods of sample preparation: solid-phase extraction and microwave decomposition. As the result of analysis of heavy metals Fe, Zn, Rb, Cu, Ni, Al, Mn content using these sample preparation methods the following conclusions are drawn: maximum extraction of heavy metals is achieved by using microwave decomposition method.Aim. The purpose of this work was to compare the methods and conditions for the sample preparation of biological samples for the determination of the content of heavy metals using atomic emission spectrometry.Materials and methods. The object of the study to determine the content of heavy metals (Zn, Rb, Cu, Ni, Al, Mn) was the liver of golden hamsters of both sexes weighing 60–145 g of the type Golden Syrian SPF category, obtained from the Federal Research Center Institute of Cytology and Genetics, Siberian Branch of Russian Academy of Sciences (Novosibirsk). Quantitative determination of heavy metals in biological samples was carried out on an Agilent 4100 atomic emission spectrometer with a microwave plasma (Agilent Technologies, USA).Results and discussion. Comparison of the content of elements in the sample using the sample preparations under study showed that the maximum extraction of heavy metals from biological samples is achieved when using the method of microwave decomposition. The most complete extraction of heavy metals from biological samples is achieved by extraction within 30 minutes.Conclusion. This method warrants the maximum metal extraction, is more accurate, rapid and less labor intensive compared to other methods considered, and is suitable for determining most heavy metals.